Oral History Interview: Richard Zellner (1460), 1 of 1 - Zellner, Richard (My University, 2016)
In his 2015 interview with Maryo Gard Ewell, Richard "Dick" Zellner recalls his extensive career in music education. Zellner began playing in the Packer Band as a high school student and later attended the University of Wisconsin-Madison to pursue a graduate degree in music. The connections he made at UW helped him launch numerous music projects across the county and the world, including the electronic symphony project in Jacksonville, Florida and the Institute for Advanced Musical Studies in Switzerland.
Richard Zellner
Keywords: UW-Madison music; UW-Madison Extension; continuing education; music education; band